Budidaya Maggot Bsf (Black Soldier Fly) Sebagai Pakan Alternatif Ikan Lele - Destriman Laoli; Okniel Zebua; Asokhiwa Zega (CV. SINAR HOWUHOWU, 2024)
This community service activity aims to provide training to the community of Onozikho Village, West Gunungsitoli Subdistrict, Gunungsitoli City, regarding the cultivation of BSF (Black Soldier Fly) maggot as an alternative feed for catfish. This activity involved lecturers, staff, students of the Aquatic Resources Study Program, and the local community, held at the village hall. The training began with the provision of material on the potential of BSF maggot, followed by practical training on making maggot cultivation media. Lecture and discussion methods were applied to improve participants' understanding, which showed positive responses and active participation. The results of the activity showed that participants gained new knowledge and skills in maggot cultivation, which is expected to improve the family economy. BSF maggot cultivation is not only efficient in terms of animal feed costs, but also provides additional benefits in organic waste management. It is expected that this activity can continue with further mentoring to ensure the sustainability of maggot cultivation practices in the community.